Oligosaccharide Presentation Modulates the Molecular Recognition of Glycolipids by Galectins on Membrane Surfaces - Marta G. Lete; Antonio Franconetti; Sandra Delgado; Jesús Jiménez-Barbero; Ana Ardá (MDPI AG, 2022)
Galectins are a family of glycan binding proteins that stand out for the wide range of biological phenomena in which they are involved. Most galectin functions are associated with their glycan binding capacities, which are generally well characterized at the oligosaccharide level, but not at the glycoprotein or glycolipid level. Glycolipids form the part of cell membranes where they can act as galectin cellular receptors. In this scenario, glycan presentation as well as the membrane chemical and structural features are expected to have a strong impact in these molecular association processes. Herein, liposomes were used as membrane mimicking scaffolds for the presentation of glycosphingolipids (GSLs) and to investigate their interaction with Galectin-3 and the N-domain of Galectin-8 (Gal8N). The binding towards GM3 and GM1 and their non-silaylated GSLs was compared to the binding to the free glycans, devoid of lipid. The analysis was carried out using a combination of NMR methods, membrane perturbation studies, and molecular modeling. Our results showed a different tendency of the two galectins in their binding capacities towards the glycans, depending on whether they were free oligosaccharides or as part of GSL inserted into a lipid bilayer, highlighting the significance of GSL glycan presentation on membranes in lectin binding.